KEYNES’ CRITIQUE OF THE CLASSICAL AND NEOCLASSICAL THEORIES OF THE RATE OF INTEREST - Carvalho, André Cutrim; Carvalho, David Ferreira (Análise Econômica, 2019)
The classical theory of the rate of interest is the theory that mainstream economists inherited chiefly from Marshall, Ricardo and Wicksell, and is also this same theory that John Maynard Keynes criticizes in his General Theory for presenting an explanation centered solely on the special case of full employment. Despite the difficulties, Keynes offered a scathing critique of the theory of the rate of interest from both classical and neoclassical economists. This was only made possible because the traditional rationale of these economists remained imprisoned by the trap set by Say's Law. Therefore, within this context, the main objective of this paper is to undertake a critical analysis of Keynes regarding the classical general theory of the rate of interest, through which we may then demonstrate the points on which he was in disagreement with the neoclassical school. The main conclusion is that Keynes considered that traditional analysis is defective because it was unable to identify the independent variables of the system. Indeed, savings and investment are determined variables and not the determinants of the dynamics of the capitalist economic system. Such determined variables are the twin product of the true determinants, i.e., from the propensity to consume, from the scale of the marginal efficiency of capital and from the interest rates, and this is why the flow of investments tends to expand until the marginal efficiency of capital remains at the rate of interest.